2019
DOI: 10.1021/acs.estlett.9b00653
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Perchlorate Formation during the Electrochemical Oxidation of Perfluoroalkyl Acid in Groundwater

Abstract: Perfluorooctanoic acid (PFOA) and perfluorooctanesulfonate (PFOS) are groundwater contaminants of emerging concern due to their toxicity and persistence. Currently, there are limited destructive treatment options for this type of water. One promising approach is electrochemical oxidation (EO) using a boron-doped diamond (BDD) anode. However, during EO treatment, chloride in water is readily converted to perchlorate (ClO 4 − ), which is an endocrine disruptor. This is a common dilemma for EO techniques: anodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 35 publications
0
45
0
Order By: Relevance
“…Benzoic acid (1 mM) was spiked in the catholyte as a radical probe. 33 , 34 No degradation of BA was observed throughout 135 min of electrolysis. Therefore, the conversion of H 2 O 2 to • OH was excluded, leaving the most plausible H 2 O 2 depletion mechanism as the cathodic reduction of H 2 O 2 by CB (H 2 O 2 + 2H + + 2e – → 2H 2 O; E 0 = 1.76 V).…”
Section: Resultsmentioning
confidence: 94%
“…Benzoic acid (1 mM) was spiked in the catholyte as a radical probe. 33 , 34 No degradation of BA was observed throughout 135 min of electrolysis. Therefore, the conversion of H 2 O 2 to • OH was excluded, leaving the most plausible H 2 O 2 depletion mechanism as the cathodic reduction of H 2 O 2 by CB (H 2 O 2 + 2H + + 2e – → 2H 2 O; E 0 = 1.76 V).…”
Section: Resultsmentioning
confidence: 94%
“…Both laboratory and pilot-scale studies show that this technology could be used for efficient degradation of PFAS-containing wastewater in full-scale, but more research should be conducted to determine optimum operating conditions and to provide a cost-effective process. Furthermore, the presence of chloride in wastewater may lead to the formation of toxic by-products, i.e., chlorate and perchlorate, during EOX treatment of PFAS (Yang et al 2019), and which should also be considered before using this technology.…”
Section: Electrooxidationmentioning
confidence: 99%
“…One limitation of these groundwater studies was that they employed relatively high PFAS concentrations compared to most drinking water sources and may not reflect the range of common PFAS contamination levels (e.g., <500 ng/L according to Glassmeyer et al (2017)). Yang et al (2019) used initial PFOA/PFOS concentrations of 10 μg/L (an order of magnitude lower than conditions tested in Schaefer et al (2017)) and found 90% PFOA and PFOS removal after 0.5 h of electrooxidation, which was far less treatment time than Trautman et al's (2015) 8 h of electrolysis for 50%–80% removal. Accordingly, more research is needed to determine PFAS treatability under low initial PFAS conditions (i.e., <500 ng/L) to determine the treatment inputs needed to meet potential PFAS regulations of <70 ng/L.…”
Section: Electrochemical Treatment As a Pfas Mitigation Technologymentioning
confidence: 93%
“…Removing precursor chloride can be accomplished by nanofiltration pretreatment to concentrate trace organics (e.g., PFAS) while excluding ionic species like chloride (Urtiaga, 2021). Yang et al (2019) determined that applying 50 mM H 2 O 2 successfully inhibited perchlorate production without decreasing PFAS treatment performance. The presence of 100–1000 mM methanol in ion exchange regenerant also decreased perchlorate formation during electrooxidation without compromising PFAS treatment performance (Wang et al, 2021).…”
Section: Barriers To Implementationmentioning
confidence: 99%